Acculturation: Advances in Theory, Measurement, and Applied Research. 2003
DOI: 10.1037/10472-008
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation among ethnic minority families.

Abstract: York: Guilford F'ress. 130, C. (1990). An analysis of domestic violence in Asian American communities: A multicultural approach to counseling. In L. Brown & M. Root (Eds.), Diversity and complexity in feminist therapy (pp. 129-150). New York: Haworth Press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 113 publications
1
90
0
1
Order By: Relevance
“…Among Latinos, the level of acculturation may be central to understanding both prevalence rates and forms of IPV (Kantor, Jasinski, & Aldorondo, 1994). However, studies examining the role of Work-related IPV 12 acculturation on IPV have produced mixed findings (Chun & Akutsu, 2003;Garcia, Hurwitz, & Kraus, 2005;Jasinski, 1998;Kasturirangan, Krishnan, & Riger, 2004;Klevens, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among Latinos, the level of acculturation may be central to understanding both prevalence rates and forms of IPV (Kantor, Jasinski, & Aldorondo, 1994). However, studies examining the role of Work-related IPV 12 acculturation on IPV have produced mixed findings (Chun & Akutsu, 2003;Garcia, Hurwitz, & Kraus, 2005;Jasinski, 1998;Kasturirangan, Krishnan, & Riger, 2004;Klevens, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The role of acculturation in the experience and perpetration of IPV has been explored in various studies; however, they have produced mixed findings (Chun & Akutsu, 2003;Garcia, Hurwitz, & Kraus, 2005;Jasinski, 1998;Kasturirangan, Krishnan, & Riger, 2004;Klevens, 2007). A plethora of studies have shown that higher levels of acculturation are associated with higher rates of IPV than less acculturated Latinos (Caetano, Schafer, Clark, Cunradi, & Raspberry, 2000;Firestone, Lambert, & Vega, 1999;Ingram, 2007;Kantor, Jasinski, & Aldorondo, 1994).…”
Section: Work-related Ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…He suggested there is a need for research to understand how Mexican American women experience interactions with the health care system, with their partners, and with social institutions like religion. The use of fertility rates and epidemiological data alone will not provide the information needed to become familiar with the beliefs, experiences, and problems of these women and to design the services to respond to their needs (Chun & Akutsu, 2002). The female is at the center of the Mexican family and receives honor and prestige.…”
Section: Hispanics In the United Statesmentioning
confidence: 99%
“…Mexican origin women (Amaro, 1988;Guendelman, Malin, Herr-Harthorn, & Varlas, 2001;Chun & Akutsu, 2002). The participants recognized their mother's strength, but several expressed a desire to express their strength differently for themselves and their family.…”
Section: Emergent Themesmentioning
confidence: 99%